Cross-Side Network Effects, Brand Equity, and Consumer Loyalty: Evidence from Mobile Payment Market. Issue 3 (2nd July 2020) - Gong, Xiang; Cheung, Christy M. K.; Zhang, Kem Z.K.; Chen, Chongyang; Lee, Matthew K.O.
ABSTRACT: Given the intense competition in the mobile payment market, researchers have been exploring strategies to maintain brand equity and consumer loyalty. By considering the characteristics of mobile payment, we incorporate cross-side network effects (CNEs) and the complementarity actions (i.e., platform-application, application-service, and service-strategy complementarities) to examine mobile payment brand equity and consumer loyalty. We test the research model using survey data collected from Alipay Wallet ( n = 647) and WeChat Wallet ( n = 327). The results show that platform-application, application-service, and service-strategy complementarities positively influence brand equity, which in turn leads to consumer loyalty. In addition, service-strategy complementarity reinforces the impacts of platform-application and application-service complementarities on brand equity. This study contributes to the literature by introducing CNEs in the mobile payment context and examining the relations between CNEs, brand equity, and consumer loyalty. Furthermore, the results provide practitioners with insights into consumer loyalty in the mobile payment context.